Review of researches on smartphone applications for physical activity promotion in healthy adults - Jee, Haemi (J Exerc Rehabil, 2017)
Physical activity is known as a preventative method for preventing life-style-related diseases. Smartphone applications for health and fitness intervention have released with rapid increase of innovative technology. Reviews of recent publications on mobile application have been conducted to observe feasibility and applicability for physical activity intervention. Bibliographic searches of PubMed and ScienceDirect were conducted with key terms, ‘physical activity,’ ‘fitness,’ ‘smart-phone,’ and ‘health’ between the years 2014 and 2017 to obtain 5,087 publications. Out of 5,087 articles, five articles on sensor-based applications and five articles on user entry-based applications were obtained through the inclusion and exclusion processes. Accuracy of the physical activity assessments were reported to be high in comparison to the conventional assessment tools. The overall subject rating on the app motivational ratings were positive with high correlation between physical activity and treats and cues. The adherence rates to the apps significantly dropped prior to 3 months. Publications that elucidate feasibility and accuracy of smartphone applications that motivates physical activity seem limited with adequately conducted study designs. Large-scaled, control-compared, long-term randomized control trials should be conducted to elucidate the effects of the app interventions.